위암 환자의 위절제술 후 삶의 질 국내 연구 동향 - 이경은(Lee, Kyung Eun); 손영길(Son, Young Gil) (Asian oncology nursing, 2016)
Purpose: The aim of this study was to analyze the research trends of quality of life (QOL) after gastrectomy among gastric cancer patients in Korea and to make suggestions for future studies. Methods: A literature search was done using Pubmed, CINHAL, and Korean databases in Korean and English. Results: A total of 53 studies from 1993 to 2015 were analyzed. Of 53 papers, 6 (11.3%) were doctoral dissertations and master's theses, and 47 (88.7%) were from academic journals. All of the studies (100%) used quantitative research designs. The European Organisation for Research and Treatment of Cancer (EORTC) quality of life questionnaire (QLQ)-C30 and EORTC QLQ-STO22 were mostly used to evaluate QOL in the studies. The main research issues were varied, in particular, the most common subjects of studies were QOL related to the evaluation of treatment methods. Conclusion: Further studies about QOL after gastrectomy with gastric cancer patients need to be done with various approaches such as intervention studies to improve QOL, qualitative studies, and multidisciplinary research.